Use of Opportunistic Screening for Hypertension and Diabetes among the Patients Attendees in a Tertiary Care Hospital of Mangalore - Prajna Sharma; Ishfaq Nazir Butt; Akhin Jayachandran; Satish More; Preeval Shreya Crasta; K G Kiran (Indian Association of Preventive and Social Medicine, 2022)
Introduction: Hypertension and Diabetes are two of the most common chronic non-communicable diseases and multifactorial disorders affecting both developed and developing countries. Method: A cross sectional study was conducted for a period of 3 months among patient attendees above the age of 30 years in a tertiary care hospital of Mangalore, between July - September 2018. Data was collected from 150 patient attendees by personal interviews followed by anthropometry, blood pressure measurement and random blood sugar and entered into Microsoft excel. Analysis was done using Statistical package for social sciences (SPSS) software version 21. Results: It was seen that 72(48%) were Normotensive, 44 (29.3%) were Pre-hypertensive and 34 (22.7%) were Hypertensive while 65(43.3%) had a random blood sugar of > 140 mg/dl. There was an association between hypertension and age, gender, type of family, occupation, religion, alcohol intake, smoking habits and physical activity which was statistically significant (p< 0.05). While age more than 45 years, illiteracy, belonging to Christian faith, having a family history of diabetes mellitus and being obese/ overweight were associated with a random blood sugar of >140 mg/dl which was statistically significant (p< 0.05). It was also seen that 23(67.6%) of hypertensive attendees and 18(40.9%) of pre-hypertensive attendees also had diabetes as a comorbidity. Conclusion: Opportunistic screening of individuals for hypertension and diabetes will help in early detection of these diseases. This will help in early prevention and timely treatment.